If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-8=x+11(-2)
We move all terms to the left:
-8-(x+11(-2))=0
We calculate terms in parentheses: -(x+11(-2)), so:We get rid of parentheses
x+11(-2)
We add all the numbers together, and all the variables
x-22
Back to the equation:
-(x-22)
-x+22-8=0
We add all the numbers together, and all the variables
-1x+14=0
We move all terms containing x to the left, all other terms to the right
-x=-14
x=-14/-1
x=+14
| 3z+7+10z=7+13z+10 | | 7(10-3)=5(15-4x) | | k+3/4=-3 | | 12=4(p-17) | | 6x-21=5x+12+x | | 4=v+11/4 | | -3b+3-2b=7+4b | | g+1/2=3 | | 3=v-1/2 | | 7|x−2|=4 | | F(x)=-31 | | 3(x-2)/3=21/3 | | 3/x-1/2=1 | | X-(x/10)=120000 | | 9+5y-7=0 | | (5x^2)+10x+4=0 | | 2(3x+6)=-13+19 | | n2-5=30 | | 8x-6=3(x+1)+5×-9 | | 8(n-2)=30 | | 7x+24x=662 | | n^2=8n=-16 | | 9+5y-7=16 | | 8x6=3(×+1)+5×-9 | | 5(n-3)=17 | | X-(x/10)=110000 | | 1.4m-0.6(m-27)=2.4m | | 2(2x+2)=-4(3x-2)+5x | | 0.009/x=0.001 | | -5(x-1)=3(x+8) | | 2/3(x)-10=-12 | | 5x+8x=47(3)+54 |